Leonardo's science workshop : invent, create, and make STEAM projects like a genius - Olinger, Heidi (Leonardo's Workshop., 2019)
"The first book in a new project-based STEAM series for kids, inspired by the Science, Technology, Engineering, Art, and Math of Leonardo Da Vinci."--